Signed‐For Delivery in the Mitochondrial Matrix: Confirming Uptake into Mitochondria. Issue 3 (23rd January 2018) - Hoogewijs, Kurt; James, Andrew M.; Murphy, Michael P.; Lightowlers, Robert N.
Abstract: Mitochondria are best known for their ability to provide energy in the form of an elevated ATP/ADP ratio to the cell via oxidative phosphorylation, and impairment of mitochondrial ATP production can lead to a variety of diseases. For many of these disorders, caused by mutations in the mtDNA, classical gene therapy or gene‐editing techniques are not possible due to the difficulty of importing nucleic acids into the mitochondrial matrix where the aberrant genes are transcribed. Technical progress in this field has been severely hampered by the inability to correctly determine whether uptake into the mitochondrial matrix of nucleic acids and related oligomers has occurred. Here, the methods that have been used to determine translocation of macromolecules into mitochondria in the past are described, and some recent developments in the field are discussed. Abstract : To eliminate pathogenic mitochondrial DNA mutations, researchers have been exploring methods to modify the mitochondrial DNA content. Unfortunately, correct assessment of mitochondrial uptake is difficult due to the complexity of mitochondrial physiology. The use of (bio)chemical reactions in situ, which mark the delivered molecules after translocation to unequivocally identify and quantify uptake, is explored.